Characteristics Associated with Success for Opioid Use Disorder Treatment in Court-involved Patients - Li, Li; Bryant, Bianca M; Cenczyk, Christina; Gawronski, Brian (Archives of Clinical and Biomedical Research, 2020)
Objectives: While the Food and Drug Administration (FDA) have approved medications for opioid use disorder (MOUD), they are underutilized with patients despite established effectiveness. The aim of the present study was to characterize the effectiveness of MOUD in a community-based drug court-involved population. Methods: This is a two-year retrospective study of electronic health records data of patients at a community-based substance use treatment program who were involved in drug court and treated with MOUD from March 2018 to February 2020. Patients treated with buprenorphine products and extended-release injectable naltrexone were eligible to be in the study. Electronic medical records were used to collect patients’ demographics, clinical characteristics, and the results of urine drug screening throughout their treatment course. Results: Of the 125 patients enrolled in the study, 100 (80%) of the patients were on buprenorphine products. Females had a greater retention rate with the medication management and a higher rate of sobriety measured by negative urine tests. Gender, treatment duration, and number of clinic visits were positively associated with sobriety and a better outcome. The number of clinic visits was the best predictor of sobriety as measured by negative urine tests. Conclusions: MOUD is effective in patients involved in the drug court, although buprenorphine products are more acceptable than extended-release injectable naltrexone. Females seem to do better in terms of the retention and sobriety rates. The number of clinic visits and treatment duration are associated with better treatment outcomes.